INFLUENCE OF SPECIALIZATION ON ECONOMIC RESULTS OF PIG FARMS1 - Szymańska, Elżbieta (Acta Scientiarum Polonorum. Oeconomia, 2012)
The aim of the research presented in the article was to determine an influence of specialisation on economic results of pig farms. The analysis included 80 pig farms with large-scale production located in eight voivodeships of the greatest concentration of these animals’ rearing in Poland. In the economic and agricultural literature there are a number of specialisation’s definitions, as well as different measurement methods and criteria are applied. This hinders comparability of the gained results. Specialisation is favourable to achieving advantages resulting from the growth in production scale. In the analysed farms, the higher level of specialisation was connected with the growth of land and labour productivity, as well as increased production profitability and return on equity. Only specialized farms of great production scale are able to cope with the growing competition on pig market.